Efficient modelling and evaluation of rolling for mitigation of residual stress and distortion in wire arc additive manufacturing. - Gornyakov, Valeriy (Cranfield University, 2021)
Wire and Arc Additive Manufacturing (WAAM) is a promising technology for manufacturing large-scale parts with low costs and short lead time. One of the main challenges in applying WAAM in industry is the effective control of residual stress and distortion. It has been found that high-pressure inter-layer rolling can effectively mitigate the residual stress and distortion of WAAM components. However, the mechanism behind the mitigation efficacy is of a complex nature and has not been well understood. Finite element analysis (FEA) has proven to be a reliable and accurate method for simulating the thermo-mechanical process. The FEA simulation of large-scale inter-layer rolling is challenging due to the high computational cost and complicated coupling between WAAM and rolling. This research is based on efficient models for simulating WAAM deposition and rolling processes, and their combination for large-scale structures. The efficient modelling method is developed using a reduced-size model to determine the steady-state solution, and then mapping the solution to a full-size structure for further analysis. This method is successfully applied to study the evolution of residual stress and plastic strain during the post-build and inter-layer rolling of WAAM deposited walls. The numerical predictions are verified with experimental results. Cyclic formation of tensile residual stress occurs during the WAAM deposition, whereas inter-layer rolling counteracts the development of the residual stress. The effectiveness of roller designs is studied for reducing residual stress of the WAAM process. Compared with a flat roller, a slotted roller can induce greater longitudinal plastic strains and more effectively reduce the tensile residual stress in the WAAM wall. Removal of the clamps only results in a slight redistribution of residual stress in the post-build and inter-layer rolled WAAM components, since the rolling mitigates most of the tensile residual stresses caused by WAAM. To enhance the manufacturing efficiency, stacked-layers rolling can replace inter- layer rolling for RS and distortion mitigation in tall WAAM parts. Influences of main process parameters, such as rolling load and roller-to-component friction, on mitigation of RS and distortion are also studied. Finally, based on the understanding gained through the simulations, recommendation of an optimal rolling strategy is made for future industrial application.
Sun, Yongle - Associate Supervisor
Keywords: wire and arc additive manufacturing; efficient FE model; residual stress; plastic strain; distortion; post-build rolling; in-process rolling; large-scale part; process optimisation